2022
DOI: 10.1111/tbed.14602
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the ecological niche of naturally occurring anthrax at global and circumpolar extents using an ensemble modelling framework

Abstract: Bacillus anthracis, the causative agent of anthrax, is a spore‐forming bacterium that primarily affects herbivorous livestock, wildlife and humans exposed to direct contact with infected animal carcasses or products. To date, there are a limited number of studies that have delineated the potential global distribution of anthrax, despite the importance of the disease from both an economic and public health standpoint. This study compiled occurrence data (n = 874) of confirmed human and animal cases from 1954 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 76 publications
(157 reference statements)
2
10
1
Order By: Relevance
“…However, it is worth noting that during summer months, temperatures may still enable significant sporulation of B. anthracis [3]. In contrast, Deka et al [16] showed “very high” and “high” suitability for anthrax in parts of our northern region M, diverging from our findings. Additionally, anthrax cases in Ukraine and Belarus were reported sparingly, likely due to rigorous documentation of biothermal pits and infected burial grounds [49].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, it is worth noting that during summer months, temperatures may still enable significant sporulation of B. anthracis [3]. In contrast, Deka et al [16] showed “very high” and “high” suitability for anthrax in parts of our northern region M, diverging from our findings. Additionally, anthrax cases in Ukraine and Belarus were reported sparingly, likely due to rigorous documentation of biothermal pits and infected burial grounds [49].…”
Section: Discussioncontrasting
confidence: 99%
“…Suitable areas identified for anthrax spanned from central to eastern Türkiye, Armenia, southern Georgia, the southern Russian Federation, Bulgaria, southern and eastern Romania, Hungary, Moldova, and southern Ukraine. These areas are similar to those found by recent studies exploring the ecological niche of B. anthracis at a global scale [6,16], as well as a study specifically focused on northern latitudes [47]. Additionally, our model found anthrax-suitable areas with low uncertainty in northeast Azerbaijan, consistent with anthrax spatial clusters observed between 2000 and 2010 [48]; and the Odesa region in Ukraine, converging with a publication reporting B. anthracis in environmental samples and animal anthrax cases in this area [49].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations